The Adoption of the Electronic Health Record by Physicians - Al-Rayes, Saja A.; Alumran, Arwa; AlFayez, Weam (Methods of Information in Medicine, 2019)
Background Health information technology, especially the electronic health record (EHR) systems, improves health care quality and patient safety.Objectives This study's objectives are as follows: first, to explore the adoption of EHR systems among physicians in Saudi Arabia (with King Fahd Military Medical Complex as the location of the pilot study), and second, to identify the factors that influence these physicians' adoption of such systems.Methods This cross-sectional quantitative study is based on a paper survey that was administered to a sample of 213 physicians. The theoretical model is a version of the Technology Acceptance Model (TAM) that features the following additional variables: resistance to change, training, and social influence.Results The sample includes 133 (62%) physicians who used EHRs and 80 (38%) who did not. The main findings show that users and nonusers of the EHR system differ significantly for several factors such as perceived usefulness, perceived ease of use, social influence, and resistance to change. In addition, age, work experience, and medical specialty are significantly associated with physicians' use of the EHR system.Conclusion To increase EHR systems' adoption rate, the following elements should be improved: the systems' design, the social environments, and the physicians' awareness of the systems' benefits. This is the first study to produce a valid and reliable instrument for measuring the factors that influences physicians' use of the EHR system at a Saudi hospital in the Eastern Province. Further studies are needed to measure how these factors influence physicians' use of EHRs in other settings.
Keywords: adoption; electronic health record system; physicians; validation; instrument; technology acceptance model